Spirometry monitoring in asthmatic children in Lombardy Region, Italy - Antonio Clavenna; Massimo Cartabia; Angela Bortolotti; Ida Fortino; Luca Merlino; Andrea Biondi; Maurizio Bonati; Pietro Casartelli (BMJ Publishing Group, 2018)
Objectives To evaluate the diagnostic and therapeutic approaches in a cohort of asthmatic children before and after starting drug therapy.Methods Data were retrieved from administrative databases of the Lombardy Region. The study population was composed of 78 184 children born in the Lombardy Region in 2002 and followed until their 10th birthday.Children with at least one antiasthmatic drug prescription per year (with the exclusion of nebulised suspension/solution formulations) in 2 consecutive years and at least one antiasthmatic drug prescription after the fifth birthday were identified as potential asthmatics (PA).Each PA was monitored for a period starting from 12 months before and ending 24 months after the first prescription (index prescription, IP). During the monitoring period antiasthmatic drug prescriptions were analysed, as well as spirometry and/or specialist visits.Results A total of 59 975 children (76.7%) received ≥1 prescription of antiasthmatic drugs in their first 10 years of life, and 4475 (5.7%) were identified as PAs. In all, 24% of PAs started with short-acting β2-agonists (SABA), 23% with inhaled corticosteroids (ICS) and 20% with SABA+ICS.A total of 33% of PAs had at least one prescription for specialist visit/spirometry: 11% before and 28% after the IP. The factors associated with a greater likelihood of receiving visit/spirometry prescriptions were local health unit of residence, age and high use of asthma drugs.Conclusions Despite international guideline recommendations, spirometry monitoring is still underused in asthmatic children, even in subjects who initiated pharmacological treatment and therefore need an airway function evaluation. Moreover, the choice of drug therapy appears not always rational, since one out of four children were commenced on ICS as monotherapy.